Osteoarthritis Depression Impacts and Possible Solutions Among Older Adults: Year 2021-2022 in Review - Marks, Ray (Journal of Aging Research And Healthcare, 2022)
Background Osteoarthritis, a serious joint disease, said to represent a generally declining state of wellbeing and function among many older adults has been shown to be affected to a considerable degree by various negative beliefs and inactions rather than degradation alone. Aim This review examines the case of depression as this pertains to the older adult with osteoarthritis of one or more joints. Specifically, the most up to date information on this topic was sought, as care improvements over the past decade have not shown any impactful population wide results. Method Reviewed were relevant 2021-2022 research and review articles specifically pertaining to what is being observed currently by researchers as far as osteoarthritis-depression linkages goes, as these may reveal opportunities for more profound research, and practice-based endeavors. Results In line with 60 years of prior research, it appears a clinically important role for depression in some osteoarthritis cases cannot be ruled out. It further appears that if detected and addressed early on, many older adults suffering from osteoarthritis may yet be enabled to lead a quality life, rather than a distressing and excessively impaired state of being. Those older osteoarthritis cases requiring surgery who suffer from concomitant depressive symptoms are likely to be disadvantaged in the absence of efforts to treat and identify this psychosocial disease correlate. Conclusion Providers and researchers are encouraged to pursue this line of inquiry and begin to map clinical osteoarthritis measures with those that can track cognitive patterns, musculoskeletal, features and inflammatory reactions along with valid depression indicators among carefully selected osteoarthritis sub groups.
Keywords: Aging; Depression; Interventions; Older Adults; Osteoarthritis; Pain